2017
DOI: 10.2196/jmir.6875
|View full text |Cite
|
Sign up to set email alerts
|

Physician Rating Websites: What Aspects Are Important to Identify a Good Doctor, and Are Patients Capable of Assessing Them? A Mixed-Methods Approach Including Physicians’ and Health Care Consumers’ Perspectives

Abstract: BackgroundPhysician rating websites (PRWs) offer health care consumers the opportunity to evaluate their doctor anonymously. However, physicians’ professional training and experience create a vast knowledge gap in medical matters between physicians and patients. This raises ethical concerns about the relevance and significance of health care consumers’ evaluation of physicians’ performance.ObjectiveTo identify the aspects physician rating websites should offer for evaluation, this study investigated the aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 49 publications
3
47
1
Order By: Relevance
“…Effective feedback methods can help improve how the physician and healthcare organization meet the patient's needs (NORC 2014). One study has shown that physicians and patients agree that patients can evaluate healthcare providers based on infrastructure, staff, organization, and interpersonal skills but are not able to effectively evaluate technical skills (Rothenfluh and Schulz 2017). In the instance of Medicare accountable care organizations, measures, feedback and auditing methods incentivize physicians to use SDM (CMS 2016).…”
Section: Feedbackmentioning
confidence: 99%
“…Effective feedback methods can help improve how the physician and healthcare organization meet the patient's needs (NORC 2014). One study has shown that physicians and patients agree that patients can evaluate healthcare providers based on infrastructure, staff, organization, and interpersonal skills but are not able to effectively evaluate technical skills (Rothenfluh and Schulz 2017). In the instance of Medicare accountable care organizations, measures, feedback and auditing methods incentivize physicians to use SDM (CMS 2016).…”
Section: Feedbackmentioning
confidence: 99%
“…Some studies suggest that there is a knowledge gap between doctors and patients related to medical knowledge [ 5 ], which makes it difficult for health care consumers to accurately evaluate a physician’s medical performance. A study by Rothenfluh and Schulz [ 15 ] reports further that physicians and health care consumers are indeed reflective of their own capabilities to assess certain care aspects, especially if highly technical. The findings from this study evidence, however, that only a minority of websites present technical or medical criteria (37/143, 25.9%) to be assessed by patients, which may be a reassuring finding for doctors.…”
Section: Discussionmentioning
confidence: 99%
“…The third section on information content consisted of 25 items covering information on the professional and educational background of the physician, practice access, and contact information, as well as personal data about the doctor. These indicators were developed iteratively; first, indicators were derived from a scoping review by Victoor and colleagues [ 14 ] and a study by Rothenfluh and Schulz [ 15 ] on aspects that were cited to be for patients when choosing a physician. In a second step, during the pretest, more information items were added until saturation was reached.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[79][80][81] Patients also progressively use their voice to evaluate their physicians on online physician rating platforms, which consequently have internationally expanded in popularity and use. [82][83][84] Ratings stretch from global statements describing physicians' professionalism to specific evaluations of physician's performance covering interpersonal manner and technical competence, as we presented in our findings. Patients however often confuse physicians' performance with system issues (staff, waiting time, location), reporting their intent to return or negative sentiment without justification, which may reduce credibility and hence physicians' willingness to accept the online feedback.…”
Section: Implications For Further Researchmentioning
confidence: 88%